(untitled) (Journal of Information Technologies in Education (ITE), 2010)
This article is focused on the Insertional Modeling System developed by A.A. Letichevsky of the department 100/105 of the Glushkov Institute of Cybernetics, National Academy of Science of Ukraine, Kyiv, Ukraine. Insertion Modeling System (IMS)[1] is built on the Algebraic Programming System (APS) that also was developed by A.A. Letichevsky in 1987. On the way of implementation of ambient calculus – a process calculus devised by Luca Cardelli and Andrew D. Gordon in 1998, and used to describe and theorize about concurrent systems that include mobility.[6] In this article we are going to discuss the constructing of the framework for mobile ambients using the Insertion Modeling System.